Monitoring Of Aquatic Insects As Bioindicators Of River Pollution - Gurning, Aksay K.; Wantasen, Sofia; Moniaga, Wilson M.; Watung, Jackson F.; Turang, Deflly A. S. (Jurnal Agroekoteknologi Terapan (Applied Agroecotechnology Journal), 2026)
Aquatic insects serve as reliable indicators for water quality. This study aims to monitor and identify various types of aquatic insects as bioindicators of pollution found in the Kali Pineleng River, Pineleng District, Minahasa Regency. Sampling was carried out using kick sampling, hand picking, and sweeping techniques at three Sosongian River stations. The process of identifying aquatic insects used the identification key of McCafferty (1981); Morse et al (1994); Yule & Y. Hoi Sen (2004). After identification, the data obtained were analyzed descriptively and quantitatively using the biotic index formula and diversity index. The results of the study found eight orders of aquatic insects with a total of 263 individuals from 24 families. The Hemiptera order dominates the number of individuals, followed by Ephemeroptera and Trichoptera. Sampling was conducted at three stations showing variations in composition and number of specimens, with Station II having the largest number of individuals. The Shannon-Wiener diversity index (H’) showed a value of 1.45341, indicating moderate diversity in the aquatic insect community. In addition, the calculation of the Biotic Index (BI) at the three stations showed that the water quality was classified as "Good", reflecting the condition of the ecosystem that still supports the life of macroinvertebrates that are sensitive to pollution. Keywords: Monitoring, aquatic insects, bioindicator, river pollution Abstrak. Serangga air berfungsi sebagai indikator yang dapat diandalkan untuk kualitas air. Penelitian ini bertujuan untuk memantau dan mengidentifikasi berbagai jenis serangga air sebagai bioindikator pencemaran yang ditemukan di Sungai Kali Pineleng, Kecamatan Pineleng, Kabupaten Minahasa. Pengambilan sampel dilakukan menggunakan teknik kick sampling, hand picking, dan sweeping di tiga stasiun Sungai Sosongian. Proses identifikasi serangga air menggunakan kunci identifikasi McCafferty (1981); Morse et al (1994); Yule & Y. Hoi Sen (2004). Setelah identifikasi, data yang diperoleh dianalisis secara deskriptif dan kuantitatif menggunakan rumus indeks biotik dan indeks keanekaragaman. Hasil penelitian menemukan delapan ordo serangga air dengan total 263 individu dari 24 famili. Ordo Hemiptera mendominasi jumlah individu, diikuti oleh Ephemeroptera dan Trichoptera. Pengambilan sampel dilakukan di tiga stasiun yang menunjukkan variasi komposisi dan jumlah spesimen, dengan Stasiun II memiliki jumlah individu terbanyak. Indeks keanekaragaman Shannon-Wiener (H’) menunjukkan nilai 1,45341, yang mengindikasikan keanekaragaman moderat pada komunitas serangga air. Selain itu, perhitungan Indeks Biotik (BI) di tiga stasiun menunjukkan bahwa kualitas air diklasifikasikan sebagai "Baik", mencerminkan kondisi ekosistem yang masih mendukung kehidupan makroinvertebrata yang sensitif terhadap polusi. Kata kunci: Pemantauan, serangga air, bioindikator, polusi sungai